Marker assisted detection of TYLCV and late blight resistance in tomato (Solanum lycopersicum) - MANGAL, MANISHA; HUSSAIN, ZAKIR; LATA, SUMAN; GOSAVI, GOKUL; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2021)
Marker assisted breeding relies on the identification of genetic loci linked to desirable genes/alleles and is beingutilized for selecting desirable traits including disease resistance in a wide variety of crops. The tomato (Solanumlycopersicum L.) production worldwide has lately been threatened by outbreaks of tomato yellow leaf curl virustransmitted by the whitefly (Bemisia tabaci) and late blight caused by oomycete pathogen Phytophthora infestans(Mont.) de Bary. Resistance genes against both pathogens are available and widely used in tomato breeding throughoutthe world. Molecular markers for resistance alleles greatly enhance selection of resistant plants. For effective breedingprogramme, the validation of markers linked to resistance genes in tomato was carried out for tomato improvement.For this purpose, available markers for the tomato yellow leaf curl disease resistance gene loci Ty-2, Ty3, Ty3a andlate blight resistant loci Ph3 were validated. The assay correctly predicted the genotypes of tomato breeding linesharbouring resistance allele at each loci. Further a multiplex assay was also standardized to simultaneously detectthe presence of resistant/susceptible alleles at Ty2,Ty3 and Ty3a loci. The present study carried out in the Division ofVegetable Science, ICAR-IARI, New Delhi, demonstrates the feasibility of combining two SCAR markers (TG0302and P6-25) for detecting simultaneously three important resistance gene loci in tomato genotypes and thereby improvingthe cost and efficiency of the assay.